-2(n+1)=19+n

Simple and best practice solution for -2(n+1)=19+n equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2(n+1)=19+n equation:


Simplifying
-2(n + 1) = 19 + n

Reorder the terms:
-2(1 + n) = 19 + n
(1 * -2 + n * -2) = 19 + n
(-2 + -2n) = 19 + n

Solving
-2 + -2n = 19 + n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '-1n' to each side of the equation.
-2 + -2n + -1n = 19 + n + -1n

Combine like terms: -2n + -1n = -3n
-2 + -3n = 19 + n + -1n

Combine like terms: n + -1n = 0
-2 + -3n = 19 + 0
-2 + -3n = 19

Add '2' to each side of the equation.
-2 + 2 + -3n = 19 + 2

Combine like terms: -2 + 2 = 0
0 + -3n = 19 + 2
-3n = 19 + 2

Combine like terms: 19 + 2 = 21
-3n = 21

Divide each side by '-3'.
n = -7

Simplifying
n = -7

See similar equations:

| 3(2x+7)=-48+63 | | 2z=-4z-2 | | 3x+30=3x+30 | | (7x-3)+(12x-7)=189 | | -x+6=2x | | 3x-(x+1)=-3+4(x-5) | | -4(x+8)=18-6(x-5) | | 4.5(2r-6)-3r= | | -4+y=-3 | | 1.6x=8.32 | | -3(x+5)=7+12(x-2) | | -4(3-3x)+7x=-37-6x | | 3x-2(7-2x)=10 | | -4=v-9 | | -3(2y-5)=7(y-2) | | 7(x-7)-4=-40-6x | | -(4x-9)-(3x-7)+6=-6(x-9)-(5x+6)+5 | | Y-3=0.4(x+1) | | R+6=-14 | | 5m+0.50=11.50 | | okx^3=343 | | m+0.50=11.50 | | -8+p=6p-6-3p | | 12x+8=8x+(-20) | | 6x-36=6 | | 5(2x-3)+4=4(2x+1)-7 | | 30=7.5x^2 | | 6(6-6p)=36+5p | | x^6-5x^4+4x^2+x+8=0 | | 2z=4z-2 | | -4(3+a)-6(1-a)=-8 | | -12=4(w-5)-6w |

Equations solver categories